2021
DOI: 10.1002/smtd.202001034
|View full text |Cite
|
Sign up to set email alerts
|

Application of Micro/Nanofabrication Techniques to On‐Chip Molecular Electronics

Abstract: Molecular electronics is a promising subject to overcome the size limitation of silicon‐based electronic devices. In the past decades, various micro/nanofabrication techniques have been developed for constructing molecular junctions, and a number of breakthroughs are made in the characterizations and applications of the single‐molecule device. The history and progress are reviewed in this article, laying emphasis on the recent works on the combination of micro/nanofabrication techniques with other techniques s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…In recent times,flexible devices have gained considerable attention in comparison to silicon-based electronic devices as they can offer variable-temperature operation, mechanical flexibility,w ide-area coverage,a nd cost reliability. [117][118][119][120] In this context, the McCreery group has fabricated ah ighly robust, stable,and wide-temperature-range endurable molecular junction on electron-beam-evaporated carbon (abbreviated as eC) on af lexible and semitransparent, polyethylene terephthalate (PET). [121] Diazonium salts of anthraquinone (AQ) were electrochemically grafted to form molecular layers of thickness 2.0-5.5 nm, followed by deposition of carbon/Aut op contact (Figure 9a-c).…”
Section: Fabrication and Charge Transport In Unimolecular Andmentioning
confidence: 99%
“…In recent times,flexible devices have gained considerable attention in comparison to silicon-based electronic devices as they can offer variable-temperature operation, mechanical flexibility,w ide-area coverage,a nd cost reliability. [117][118][119][120] In this context, the McCreery group has fabricated ah ighly robust, stable,and wide-temperature-range endurable molecular junction on electron-beam-evaporated carbon (abbreviated as eC) on af lexible and semitransparent, polyethylene terephthalate (PET). [121] Diazonium salts of anthraquinone (AQ) were electrochemically grafted to form molecular layers of thickness 2.0-5.5 nm, followed by deposition of carbon/Aut op contact (Figure 9a-c).…”
Section: Fabrication and Charge Transport In Unimolecular Andmentioning
confidence: 99%
“…In addition to the efficient charge transport across the TTP films, the junction shows 78-fold enhancement of charge storage In recent times,flexible devices have gained considerable attention in comparison to silicon-based electronic devices as they can offer variable-temperature operation, mechanical flexibility,w ide-area coverage,a nd cost reliability. [117][118][119][120] In this context, the McCreery group has fabricated ah ighly robust, stable,and wide-temperature-range endurable molecular junction on electron-beam-evaporated carbon (abbreviated as eC) on af lexible and semitransparent, polyethylene terephthalate (PET). [121] Diazonium salts of anthraquinone (AQ) were electrochemically grafted to form molecular layers of thickness 2.0-5.5 nm, followed by deposition of carbon/Aut op contact (Figure 9a-c).…”
Section: Fabrication and Charge Transport In Unimolecular Andmentioning
confidence: 99%
“…Several progress reviews in the field of molecular electronics have been reported in terms of device platform, yield, and electrical functionalities. [27][28][29][97][98][99][100][101][102][103][104] For example, Xiang et al provided an overview of molecular junctions at the level of the device platform and charge transport phenomena. [27] Various molecular junction platforms and theoretical simulations were described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al reviewed various micro/nanofabrication strategies for creating molecular junctions with a single molecule that enables desirable functionality. [101] They discussed the difficulties and opportunities associated with the fabrication of single molecular devices. Lastly, Xie et al presented various single molecular junction platforms for monitoring and manipulating the physical and chemical behavior of molecular components.…”
Section: Introductionmentioning
confidence: 99%